Phononic metamaterial for efficient sound attenuation applications. Issue 2 (June 2022) - Aravantinos-Zafiris, Nikos; Sigalas, Mihail M; Katerelos, Dionysios TG
In this work, a phononic metamaterial suitable for several sound attenuation applications is numerically and experimentally examined. The proposed structure consists of a combination of spheres in a face-centered cubic arrangement with rods that form the Yablonovite Structure. The Sound Transmission Loss of the structure is experimentally examined. In addition, numerical calculations of the Sound Transmission Loss were performed by using the Finite Element Method. The research includes experimental and numerical validation of different geometric parameters of the structure. The Sound Transmission Loss of the proposed structure found to have wide values over a wide frequency range of the audio spectrum. The findings of this research strongly indicate that the proposed metamaterial is a powerful candidate for efficient sound attenuation applications.